Contribution of investment in health and cancer control to economic growth in Commonwealth countriesResearch in context - Rifat Atun; Jan Ludwig Fries; Karla Hernandez-Villafuerte; Malina Müller; Dennis Ostwald; Maike Schmitt (EClinicalMedicine)
Summary: Background: There are three broad mechanisms through which health investments yield economic benefits. First, health investments in cost-effective innovations help improve health outcomes and reduce healthcare costs in a health system. Second, investments in health can help improve health and wellbeing of individuals. A healthier population is economically more productive, with a longer productive life and reduced absenteeism and presenteeism. Third, an important but often-overlooked mechanism is the benefit of health investments on the broader economy through influences on supply and demand across various other sectors of a country’s economy. We examine the third mechanism in selected Commonwealth countries. Methods: We provide an analysis and estimates of GVA growth and employment effects of the Health Economy for four Commonwealth countries, namely India, Nigeria, Malaysia and the United Kingdom in 2022. Drawing on a conservative ‘static estimation approach’, whose bases are on the Health Economy Reporting, to provide country-specific assessment of the return on investment in cancer services and cancer prevention in the UK, for which data are available, as an illustrative ‘use case’. For cancer prevention, we examine investments in vaccination for Human Papilloma Virus. Findings: In our analysis, the Gross Value Added (GVA) generated by the Health Economy in the UK amounted to about US$295 billion (8.9% of GDP; the largest sector by size) in 2022, with around US$171 billion of GVA (5.2% of GDP) generated in adjacent sectors, and through these two effects generating additional induced consumption of US$217 billion of GVA (6.6% of GDP). In India, Malaysia, and Nigeria, in 2022, total GVA generated by the Health Economy, adjacent sectors and through induced income accounted for 9.9%, 9.8% and 7.0% of the GDP respectively. In the UK, US$134 million of investment in HPV vaccination generated US$247 million of GVA in total and 2000 jobs. Whereas in India US$756 million of investment in HPV vaccination produced US$ 1149 million in total GVA and generated 155,000 jobs. Interpretation: The assessment of four Commonwealth countries reveals that the Health Economy contributes substantially to economic growth and generates substantial employment. These contributions extend beyond the health sector itself, reaching adjacent sectors along the health value chain and inducing effects throughout the broader economy. Investment in cancer prevention generates high returns with substantial addictions to GVA and employment. Funding: No external funding. Self-funded by Harvard University and Wifor Institute.